Teachers’ Training in Digital Tools and Their Arts and Design Program Management in a Science and Technology University in Yunnan Province, China - Lu, Mingde (Pacific International Journal, 2025)
This study examines the relationship between teachers’ training in digital tools and their management of arts and design programs at a science and technology university in Yunnan Province, China. Using a descriptive-comparative-correlational design, the research surveyed 81 faculty members to assess their digital competencies and project management skills. Findings indicate that while teachers demonstrate confidence in learning new technologies and integrating digital tools into lesson planning, challenges remain in subject-specific proficiency, hands-on classroom application, and fostering students’ independent use of digital resources. The study also reveals strong correlations between digital training and effective project management, particularly in communication, creativity, and ethical practices. However, areas such as equitable technology access and student self-assessment require further development. Demographic factors such as age, sex, and years of service showed no significant influence on teachers’ self-assessments, though educational attainment impacted perceptions of knowledge and professional development. The study concludes that targeted training programs, institutional support, and ethical digital integration are essential for enhancing both teaching effectiveness and program management in arts and design education. Recommendations include ongoing professional development, practical workshops, and structured peer collaborations to strengthen digital competencies and project leadership.